Wild bison as ecological indicators of the effectiveness of management practices to increase forage quality on open rangeland. (September 2015) - Ranglack, Dustin H.; du Toit, Johan T.
Highlights: Habitat manipulations are used to improve rangeland conditions for grazers. We monitored use by bison of burned, chained, and unmanipulated habitats. Bison fecal N was highest on previously burned rangeland. Bison sample rangeland heterogeneity more extensively than cattle do. Free-ranging bison are effective bioindicators of rangeland response to manipulation. Abstract: Habitat manipulations through the use of fire or mechanical treatments are often used to combat woody plant encroachment and increase foraging opportunities for wildlife and livestock. This creates spatial heterogeneity in habitat quality that large herbivores should respond to in ways predicted by ideal free distribution theory. We monitored free-ranging bison to test whether, (1) manipulated habitats offer higher quality forage than habitats in undisturbed rangeland, (2) bison respond through changes in herd composition or activity to differences in habitat quality, and (3) burned and mechanically treated habitats offer similar forage qualities. We found that habitat types burned ∼10 years ago continue to produce higher quality forage as evidenced by bison fecal N concentration (14.4 g kg −1 dry mass) than open (10.5 g kg −1 ), closed (10.6 g kg −1 ), or mechanically manipulated habitats (11.7 g kg −1 ). Bison herd composition and activity did not vary across habitat types within seasons, despite some between-season variation in overall group composition with sexual segregation being most evident before mid-summer. For semi-arid rangelands encroached with woody vegetation (e.g. piñon–juniper in the western USA) our evidence from free-ranging bison indicates that burning results in higher quality forage than occurs in both mechanically manipulated and undisturbed habitats. Bison roam widely from water, sample available vegetation continuously, and are long-lived gregarious animals that learn to exploit the spatiotemporal heterogeneity in their large home ranges. Bison also have very similar diets to cattle and so, where bison and cattle are allowed to comingle, we suggest the foraging parameters of free-ranging bison are effective ecological indicators of rangeland quality for both bison and cattle.